Earnings Volatility and Leverage on Accounting Conservatism: Evidence from Indonesian Food and Beverage Companies - Delyla, Aisha; Kusumawardani, Anisa (Journal of Economics and Management Scienties, 2026)
This research examines the effect of earnings volatility and leverage on accounting conservatism in food and beverage sub-sector companies listed on the Indonesia Stock Exchange. This research adopts a quantitative approach using secondary data from financial statements for the 2019-2023 period. The population consists of food and beverage sub-sector companies listed on the IDX, with a sample of 23 companies selected through purposive sampling. The independent variables are earnings volatility, measured by the standard deviation of EBIT, and leverage, measured by the debt-to-assets ratio. The dependent variable is accounting conservatism, measured using the Givoly and Hayn model. Hypothesis testing was conducted using multiple linear regression analysis with SPSS version 27. The findings indicate that earnings volatility has a negative and significant effect on accounting conservatism, suggesting that management tends to reduce conservatism application during high earnings fluctuations to avoid negative investor perceptions and maintain reporting stability. Meanwhile, leverage shows a positive and significant effect on accounting conservatism, indicating that companies with high leverage implement conservatism as a response to creditor monitoring demands.